Retrospective study of 20 cats surgically treated for insulinoma. Issue 1 (20th September 2022) - Veytsman, Stan; Amsellem, Pierre; Husbands, Brian D.; Rendahl, Aaron K.; Bergman, Philip J.; Chanoit, Guillaume; Hickey, Colleen; Cash, Kristy R.; Maritato, Karl C.; Collivignarelli, Francesco; Kirpensteijn, Jolle
Abstract: Objective: To report the clinical signs, histopathology results, and prognostic factors for outcomes following excision for feline insulinoma (INS). Study design: Retrospective study. Sample population: Twenty client‐owned cats. Methods: Medical records from 2006 to 2020 were reviewed by Veterinary Society of Surgical Oncology members for cats with hypoglycemia resulting from INS, with surgical excision and follow up. Clinical signs and histopathology results were summarized. Factors potentially related to disease‐free interval (DFI), disease‐related death (DRD), and overall survival time (OST) were analyzed with a Cox proportional hazards regression analysis. Results: All cats were hypoglycemic on presentation with neurologic signs in 18 out of 20 and inappropriate insulin levels in 12/13. Excision of insulinomas resulted in immediate euglycemia or hyperglycemia in 18 cats. Eighteen cats survived to hospital discharge. The median time to death or last postoperative follow up was 664 days (range: 2‐1205 days). Prognostic factors included age at presentation (for DFI); time to postoperative euglycemia (for DRD); preoperative and postoperative serum blood glucose concentrations; metastasis at the time of surgery (DFI and DRD), and histopathologic tumor invasion (for OST). The median OST for all cats was 863 days. The 1‐, 2‐ and 3‐year survival rates were 75%, 51%, and 10%, respectively. Conclusion: Excision of insulinoma resulted in euglycemia or hyperglycemia in most cats. Negative prognostic factors included young age, low serum glucose concentrations, metastasis at time of surgery, tumor invasion, and shorter time to euglycemia. Clinical significance: Surgical excision resulted in survival times comparable to those of canine INS.